Why do people visit or avoid public green spaces? Insights from an online map-based survey in Bochum, Germany - Romelli, Claudia; Anderson, Carl C.; Fagerholm, Nora; Hansen, Rieke; Albert, Christian (Taylor and Francis Ltd., 2025)
Public green spaces (PGS) have the capacity to fulfil the needs and interests of diverse groups of urban dwellers and thus contribute to their well-being. However, PGS designers and managers usually lack spatially disaggregated information on how PGS is used, by whom, and for what reasons. This study aims to assess spatial PGS visitation and avoidance patterns and their respective determinants using the city of Bochum, Germany as a case study. The research design consists of the design and application of an online map-based survey (public participation GIS–PPGIS) targeting residents and subsequent statistical and spatial analyses. Survey data include 807 completed surveys with 1084 marked visited points and 329 marked avoided points across the study area. Our results show both spatial clusters and co-occurrence of PGS visitation and avoidance. Respondents visit and avoid PGS for different reasons, which are linked to societal determinants (e.g. exercising or resting and relaxing), physical determinants (e.g. amount of grassy area or presence of trash) and sociodemographic background. Although reasons for PGS visitation and avoidance show limited spatial variation across different PGS, we find variation when disaggregating by gender and age. Insights generated can provide useful guidance for urban planners and policy makers for prioritising design and management actions to address reasons for avoidance of PGS, enhance their perceived quality and benefits, and craft PGS management concepts that better address place-specific conditions and preferences of different sociodemographic groups.